Beyond the pitch: Antecedents to customer loyalty in South Africa's advertising industry - Du Preez, Craig (The IIE, 2025)
Customer loyalty in the South African advertising industry has been conceptually underdeveloped with existing frameworks either outdated or adapted from broader service and business-to-business (B2B) contexts. These frameworks fail to consider the relational and strategic requirements of client-agency relationships. Accordingly, this study sought to identify and codify the antecedents of customer loyalty within advertising agency relationships and to propose a contextually relevant conceptual framework. A deductive qualitative research design was adopted, guided by a directed qualitative content analysis approach. Semi-structured interviews were used to collect data from purposively sampled agency clients and advertising executives. Data were analysed using priori coding based on existing customer loyalty theory to capture the lived experiences of participants. The analysis produced a theoretically-grounded and contextually-refined conceptual framework linking service quality, relational drivers, satisfaction, perceived value and switching costs with agency-specific antecedents. The findings reveal that customer loyalty within the advertising industry is not transactional but relationally co-constructed, underpinned by trust, transparent communication and strategic alignment. Perceived value was the strongest antecedent of customer loyalty. The study concludes that sustained loyalty depends on an agency’s ability to remain relevant and supportive over time, particularly during periods of change or pressure. It was recommended that advertising agencies prioritise account management quality, emotional trust and proactive alignment with client goals to maintain relevance and longterm partnership value.
Keywords: Customer loyalty; B2B industry; Advertising; Service quality; Perceived value